1999
DOI: 10.1021/jm991010h
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationships and Molecular Modeling Analysis of Flavonoids Binding to the Benzodiazepine Site of the Rat Brain GABAA Receptor Complex

Abstract: The affinities for the benzodiazepine binding site of the GABA(A) receptor of 21 flavonoids have been studied using [(3)H]flumazenil binding to rat cortical membranes in vitro. We show that flavonoids with high affinity for the benzodiazepine receptor in vitro spanning the whole efficacy range from agonists (1q) to inverse agonists (1l) can be synthesized. The receptor binding properties of the flavonoids studied can successfully be rationalized in terms of a comprehensive pharmacophore model recently develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
113
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(122 citation statements)
references
References 21 publications
4
113
0
2
Order By: Relevance
“…In addition, interactions with the benzodiazepine binding sites of GABA-A receptors and with adenosine receptors [48,117] have been reported. For example, the stilbene resveratrol and the citrus flavanones, hesperetin and naringenin, have been reported to have inhibitory activity at a number of protein kinases Fig.…”
Section: Flavonoid Interactions With Neuronal Signalling Cascadesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, interactions with the benzodiazepine binding sites of GABA-A receptors and with adenosine receptors [48,117] have been reported. For example, the stilbene resveratrol and the citrus flavanones, hesperetin and naringenin, have been reported to have inhibitory activity at a number of protein kinases Fig.…”
Section: Flavonoid Interactions With Neuronal Signalling Cascadesmentioning
confidence: 99%
“…They may also interact directly with mitochondria, for example, by modulating the mitochondrial transition pore (mPT), which controls cytochrome c release during apoptosis [65,169], or by modulating other mitochondrial associated pro-apoptotic factors such as DIABLO/smac [64,165]. Potential interactions with the mPT are especially interesting, as the transition pore possesses a benzodiazepine-binding site where flavonoids may bind [48,117] and influence pore opening and cytochrome c release during apoptosis.…”
Section: Flavonoid Interactions With Neuronal Signalling Cascadesmentioning
confidence: 99%
“…Other authors reported beneficial effects of G. biloba extract against beta-amyloid-mediated neurotoxicity in primary hippocampal neurons [11,57] and implicated antioxidant activities and the modulation of intracellular calcium levels in PC12 cells [209] as possible mechanisms of action. Other lines of research focused on the binding of flavonoids such as apigenin, naringenin, kaempferol, quercetin-3-O-glucoside and others to benzodiazepine binding sites [149] of different receptors including the GABA-A-receptor [52,132] and adenosine receptors [139], and investigated their anxiolytic potential [149] as a possible mechanism of action in the CNS. Bastianetto et al report that antioxidant effects are not the only mechanism of flavonoid-mediated protection against neuronal death and show attenuation of NO • -induced activation of protein kinase C (PKC) by G. biloba [12] and resveratrol [13] to be partially involved in the protection against neurotoxicity.…”
Section: Flavonoids: Neuroprotective Agents In Vivo and In Vitro?mentioning
confidence: 99%
“…Interestingly, the mPTP possesses a benzodiazepine binding site and the binding of ligands such as PK11195 [36,55] and antagonists like flumazenil [69] have been shown to modulate the mPTP. Since flavonoids have been reported to bind to benzodiazepine binding sites of GABA-A and adenosine receptors [52,132], they might also exert an effect on the mPTP and, therefore, modulate cytochrome c release. In addition flavonoids have been found to bind to ATP-binding sites of proteins [43] such as the mitochondrial ATPase [53], calcium plasma membrane ATPase [10] protein kinase A [164], PKC [117] and topoisomerase [17] all of which must be considered in intracellular responses to oxidative insults.…”
Section: Flavonoids: Neuroprotective Agents In Vivo and In Vitro?mentioning
confidence: 99%
“…Flavonoids have the potential to bind to the ATPbinding sites of a large number of proteins (122) including mitochondrial ATPase (123) , Ca plasma-membrane ATPase (124) , protein kinase A (125) , protein kinase C (118,(126)(127)(128)(129) and topoisomerase (130) . In addition, interactions with the benzodiazepine-binding sites of GABA A receptors and with adenosine receptors (131,132) have been reported. For example, the stilbene resveratrol and the citrus flavanones hesperetin and naringenin have been reported to have inhibitory activity at a number of protein kinases (133)(134)(135) .…”
Section: How Might Flavonoids Act To Induce Neuro-cognitive Changes?mentioning
confidence: 99%